Prevention of adverse drug reactions in intensive care patients by personal intervention based on an electronic clinical decision support system - Bertsche, Thilo; Pfaff, Johannes; Schiller, Petra; Kaltschmidt, Jens; Pruszydlo, Markus Gerhard; Stremmel, Wolfgang; Walter-Sack, Ingeborg; Haefeli, Walter E.; Encke, Jens (Intensive care medicine, 2010)
We investigated the effect of written drug information for senior clinicians on the incidence of drug-drug interactions (DDIs) and DDI-related adverse events in intensive care patients.
Gesehen am 27.01.2023